Compliance With International Environmental Standards And Expectations: Review Of International Developments - Introduction - J. Glazewski (The Southern African Institute of Mining and Metallurgy, 2000)
The mining industry in South Africa has developed its own environmental guidelines in the form of an Aide-Mémoire1,which is an extension of the previous rehabilitation provisions to include all aspects of the environment and all phases of a mining operation. This development, at the time, recognized an international trend towards the formalization of environmental management in mining practice, which resulted from the realization of the large environmental liabilities that mines could face, particularly on closure. Over the past decade the international environmental focus in the mining industry has moved from operational management, to the reduction of liability on mine closure. Mine closure guidelines are being developed internationally by nations (for example, SRK, 19982) and by large mining groups (for example, Rio Tinto, 19983). In South Africa the Department of Minerals and Energy (DME) is presently reviewing the Aide-Mémoire to bring it in line with international and local developments and a separate mine closure plan is being considered.